2022
DOI: 10.1108/jsit-11-2020-0249
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Facebook adoption and its impact on service-based small and medium enterprise performance in northwestern Nigeria

Abstract: Purpose This study aims to examine the determinants of Facebook adoption and its impact on the performance of service-based small and medium enterprises (SMEs) in northwestern Nigeria. The mediating effect of Facebook adoption between the determinants of Facebook adoption and the performance of the SMEs was examined. Design/methodology/approach A comprehensive framework was built using the technology – organisation–environment framework integrated with the resource-based view theory. Data were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…This signifies that government encouragement captures a substantial role in firms' embracement toward ORE. This is in agreement with recent studies [30,55], confirming that government support is necessary for generating policies, financial and non-financial assistance, and this reinforces firm decisions of ORE utilization. However, upon validation, it appears that the relationship between competitive pressure and ORE adoption is not supported.…”
Section: Structural Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…This signifies that government encouragement captures a substantial role in firms' embracement toward ORE. This is in agreement with recent studies [30,55], confirming that government support is necessary for generating policies, financial and non-financial assistance, and this reinforces firm decisions of ORE utilization. However, upon validation, it appears that the relationship between competitive pressure and ORE adoption is not supported.…”
Section: Structural Modelsupporting
confidence: 92%
“…El-Haddadeh et al [30] argued that it inspires top-tier managers to understand the benefits and to incite their willingness toward big data analytics. Abdullahi et al [55] examined a Facebook adoption model among servicebased enterprises and revealed the strong relationship between government support and Facebook adoption, as the government provides training assistance programs, tax subsidies, and data subscription subsidies. Overall, governmental financial and non-financial support would increase the firm probability of innovation acceptance.…”
Section: Environmental Context-related Factors and Ore Adoptionmentioning
confidence: 99%
“…Past studies on technology adoption (Abdullahi et al, 2022;Alshamaila et al, 2013;Awa et al, 2017;Eze, Chinedu-eze, Bello, Inegbedion, et al, 2019;Lai, 2017;Molinillo & Japutra, 2017;Shetty & Panda, 2022) have shown the importance of the design of the system or technology itself on the technology adoption decision of SMEs. This is because, the results of these studies have concluded that technology adoption is positively impacted by the relevance of the technology at hand for the user to perform his or her task, its usefulness as well as its degree of complexity.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…But how do we address the technological anxiety and the sense of control or lack thereof (perceived behavioral control [PBC]) that affects student adoption? Not much research has explored how these factors affect technology adoption in student circles (Abdullahi et al , 2022). If the COVID-19 pandemic taught us anything, it showed us that face-to-face-only education is something of the past.…”
Section: Introductionmentioning
confidence: 99%